Early-life antibiotic exposure increases the risk of childhood overweight and obesity in relation to dysbiosis of gut microbiota: a birth cohort study - Ping Li; Xuelian Chang; Xiaoyu Chen; Chuan Wang; Yu Shang; Dongyi Zheng; Kemin Qi (BMC, 2022)
Abstract Background Early-life antibiotic exposure is associated with the development of later obesity through the disruption of gut microbiota in the animal models. However, the related epidemiological evidence is still conflicting. Methods A birth cohort was consisted of 2140 mother-infant pairs in Chaoyang District Maternal and Child Health Care Hospital in this study. Here, their available antibiotic exposure during the first one year of life was ascertained using a open-ended questionnaire and related anthropometric parameters from the health screening program. The compositions of gut microbiota were comprehensively analyzed by16S rRNA high throughput sequencing. Then the spearman correlations were performed by the multiple covariance-adjusted regressions between the antibiotic exposure with anthropometric parameters and compositions of gut microbiota. Results Among the 2140 subjects, the antibiotic exposure during the first one year of life was 53.04%, mainly by Cephalosporins (53.39%) and Erythromycins(27.67%) for the treatment of respiratory tract infection (79.56%), which were not significantly different among the subgroups. Compared to the control group, both childhood overweight and obesity at two and a half years were higher in the antibiotic exposed group, with higher percents of Faecalibacterium, Agathobacter and Klebsiella, and lower percentage of Bifidobacterium. Moreover, there were positively potential associations between early-life antibiotic exposure with the accelerated anthropometric parameters and disruption of Faecalibacterium, Agathobacter, Klebsiella and Bifidobacterium at two and a half years. Conclusion These above results proved that early-life antibiotic exposure was positively associated with the accelerated childhood overweight and obesity from one year to two and a half years by impacting the disorders of Faecalibacterium, Agathobacter, Klebsiella and Bifidobacterium, which would propose the theoretical basis for rationalizing the personalized antibiotic exposure among the infants to truly reflect the fairness of public health.